IMPLEMENTATION OF EDUCATIONAL STRATEGIES IN THE FACE OF DISRUPTION OF THE INDUSTRIAL REVOLUTION 4.0 TOWARDS COMMUNITY RESOLUTION 5.0 - Rizal, Samsul; Muliadi, Mul; Kristyanto, Dian; Paraira Parada, Natalino; Puspita, Yenda (Jurnal Review Pendidikan dan Pengajaran, 2023)
The goal of this research is to explain how Educational Policy is carried out in accordance with Economic Era 4.0 and Societies 5.0 resolves. Until the Build Society 5.0 idea came. 4.0 industrial revolution the study's results suggest that the technology's role in the 4.0 industrial revolution should be expanded to construct a society 5.0 model of a wealthier and civilized human existence. It is vital to adapt relevant learning patterns for Indonesians in particularly to train people for the 4.0 industrial revolution and society 5.0. Eight national curriculum standard school reform policies should be reinforced in their execution in Education Management. A new paradigm of school administration based on information artificial intelligence and technology must be established to assist the deployment of a learning system in the period of the Fourth Industrial Revolution.